2007
DOI: 10.1016/j.rmed.2006.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle structure and function in response to electrical stimulation in moderately impaired COPD patients

Abstract: NMES may promote a modest degree of type II muscle fibre hypertrophy in COPD patients with well-preserved functional status. These micro-structural changes, however, were not translated into increased volitional strength in this sub-population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 29 publications
2
106
0
4
Order By: Relevance
“…Small controlled studies with this technique in severe and even bed-bound COPD patients have been reported [29][30][31][32][33][34][35]. NMES must be delivered according to specific protocols of intensity, frequency, duration and waveform of the stimulus in order to target optimal muscle response.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Small controlled studies with this technique in severe and even bed-bound COPD patients have been reported [29][30][31][32][33][34][35]. NMES must be delivered according to specific protocols of intensity, frequency, duration and waveform of the stimulus in order to target optimal muscle response.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…A number of studies have evaluated NMES in severe COPD patients with significant baseline exercise impairment [30][31][32][33][34]. The electrical stimulus frequency ranged 10-50 Hz.…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…However, the demonstrated results provide a basis for implementing NMES in clinical practice in patients with COPD [25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The sessions were usually performed 5 [25][26][27][28][29] or 4 [7] times a week. The total time of NMES application amounted to 4, 5 or 6 weeks [25][26][27][28][29][30][31][32]. The value of electric current used depended on the specific tolerance of the patient.…”
Section: Application Of Nmes In Patients With Chronic Obstructive Pulmentioning
confidence: 99%
See 1 more Smart Citation